Saving Sky - Stanley, Diane (New York : Harper, 2010)
In an America that has suffered continual terrorist attacks since 9/11, seventh-grader Sky stands up for what is right and helps a classmate of Middle Eastern descent, although doing so places her and her family at great risk.
620
Keywords: Conduct of life -- Fiction; Self-realization -- Fiction; Terrorism -- Fiction; Prejudices -- Fiction; Middle Eastern Americans -- Fiction; Family life -- New Mexico -- Fiction; New Mexico -- Fiction